TRUS-Guided Target Biopsy for a PI-RADS 3–5 Index Lesion to Reduce Gleason Score Underestimation: A Propensity Score Matching Analysis - Chung, Jae Hoon; Park, Byung Kwan; Song, Wan; Kang, Minyong; Sung, Hyun Hwan; Jeon, Hwang Gyun; Jeong, Byong Chang; Seo, Seong Il; Jeon, Seong Soo; Lee, Hyun Moo (Frontiers in Oncology, 2022)
Background: Magnetic resonance imaging (MRI) and transrectal ultrasound (TRUS)-guided cognitive or image fusion biopsy is performed to target a prostate imaging reporting and data system (PI-RADS) 3-5 lesion. Biopsy Gleason score (GS) is frequently underestimated compared to prostatectomy GS. However, it is still unclear about how many cores on target are necessary to reduce undergrading and if additional cores around the target may improve grade prediction on surgical specimen.. Purpose: To determine the number of target cores and targeting strategy to reduce GS underestimation. Materials and Methods: Between May 2017 and April 2020, a total of 385 patients undergoing target cognitive or image fusion biopsy of PI-RADS 3-5 index lesions and radical prostatectomies (RP) were 2:1 matched with propensity score using multiple variables and divided into 1-4 core (n=242) and 5-6 core (n=143) groups which were obtained with multiple logistic regression with restricted cubic spline curve. Target cores of 1-3 and 4-6 were sampled from central and peripheral areas, respectively. Pathologic outcomes and target cores were retrospectively assessed to analyze the GS difference or changes between biopsy and RP with Wilcoxon sign rank test. Results: The median of target cores was 3 and 6 in the 1-4 core and 5-6 core groups, respectively (p<0.001). Restricted cubic spline curve showed that GS upgrade was significantly reduced from the 5th core and there was no difference between 5th and 6th cores. Among the matched patients, 35.4% (136/385; 95% confidence interval, 0.305-0.403) had a GS upgrade after RP. The GS upgrades in 1-4 core and 5-6 core groups were observed in 40.6% (98/242, 0.343-0.470) and 26.6% (38/143, 0.195-0.346), respectively (p=0.023). Although there was no statistical difference between the matched groups in terms of RP GS (p=0.092), 5-6 core group had significantly higher biopsy GS (p=0.006) and lower GS change from biopsy to RP (p=0.027). Conclusion: Five or more target cores sampling from both periphery and center of an index tumor contribute to reduce GS upgrade.